Enhancing Exclusive Breastfeeding Outcomes through Rumah Asik: Community-Based Counseling Intervention in Makassar, Indonesia - Aswita Amir; Chaerunnimah Chaerunnimah; Fatmawaty Suaib; Rudy Hartono (Jurnal Kesehatan Manarang, 2026)
Background: Exclusive breastfeeding coverage remains suboptimal, partly due to limited family involvement and counseling that primarily targets mothers. Family-based interventions such as Rumah ASIK may improve breastfeeding outcomes; however, evidence on their effectiveness is still limited. Objective: This study aimed to examine the effect of counseling on breastfeeding practices, complementary feeding, infant health status, and growth. Methods: A pre-experimental study with a post-test only control group design was conducted in Makassar, Indonesia. A total of 50 participants were included, consisting of 20 mothers in the intervention group and 30 in the control group. The intervention involved structured counseling provided during pregnancy and early infancy. Data on exclusive breastfeeding, complementary feeding practices, infant health status, and growth were collected using questionnaires and interviews. Statistical analyses were performed using Chi-square and Mann–Whitney tests with a significance level of p<0.05. Results: The prevalence of exclusive breastfeeding was significantly higher in the intervention group compared to the control group (p<0.05). However, no significant differences were observed in complementary feeding practices, infant health status, or growth between the two groups. Conclusion: Counseling through the Rumah ASIK approach effectively improves the prevalence of exclusive breastfeeding but does not significantly influence complementary feeding practices, infant health status, or growth.